„Оживеаната“ расказност во ерата на методолошкиот плурализам (Атанас Вангелов „Теорија на прозата“) - Tasevska Hadji Boshkova, Iskra (Филолошки факултет „Блаже Конески“, 2010)
Inquiring the problem of narration and narratology in this contemporary epoch rich with its post-methods (postmodern, poststructural, psychoanalytic, feminist, postcolonial, etc.), and analyzing the interest in narrativity as tradition even before initializing the term “narratology” by Tzvetan Todorov in “Grammar of Decameron” (1969), we are witnesses of the unstoppable actualization and reactualization of narration as narratological fundamental. It is understandable why it is necessary to reestablish and depict the importance of basic narratology texts (first published in Macedonian in “Teorija na prozata”, Skopje, 1996), as well as to reaffirm the intelligibility of such scholar as Atanas Vangelov, who composed the preface to this publication, uniting following theoretical acknowledgments into metatheoretical basis and dialogization (syncronical and dyacronical). It is important to gaze at the impulses and reflections that this unique translation provoked in the Macedonian literary science, rendering Atanas Vangelov highly professional individual into the “praxis” of total.
Keywords: narratology, narrativity, dialogization, taxonomy, actantial model, distributive and intergrative level